Trans-differentiation of Jdp2-depleted Gaba-receptor-positive cerebellar granule cells to Purkinje cells - Chia-Chen Ku; Jia-Bin Pan; Kenly Wuputra; Wen-Li Hsu; Kohsuke Kato; Michiya Noguchi; Yukio Nakamura; Shigeo Saito; Cheng-Yu Tsai; Ying-Chu Lin; Deng-Chyang Wu; Chang-Shen Lin; et al. (Cell Death Discovery)
Abstract The Jun dimerization protein (Jdp2) gene is active in mouse cerebellar granule cells and its protein product plays a crucial role in the formation of the cerebellum lobes through programmed cell death. However, the role of Jdp2 in cellular differentiation and pluripotency in the cerebellum, and the effect of the antioxidation reaction on cell plasticity, remain unknown. N-acetyl-l-cysteine (NAC) induced the early commitment of the differentiation of granule cell precursors (GCPs) to neurons, especially Purkinje cells, via the γ-aminobutyric acid type A receptor α6 subunit (Gabra6) axis; moreover, Jdp2 depletion enhanced this differentiation program of GCPs. The antioxidative effect of NAC was the main driving force of this decision toward the neural differentiation of the GCP population in the presence of Gabra6 in vitro. This implies that antioxidative drugs are effective agents for rescuing oxidative-stress-induced GCP damages in the cerebellum and commit this Gabra6-positive cell population toward differentiation into Purkinje cells.